Status of school libraries and developmental issues in Pakistan: A case study of public high schools. Issue 4 (17th December 2018) - Tabassum, Faiza; Batool, Syeda Hina; Ameen, Kanwal; Hassan, Mehreen
Abstract : Purpose: The purpose of this paper is to highlight the status (information services, infrastructure, budget, collection and staffing) of public girls' high school libraries of the Lahore city. Lahore is the second largest and hub of educational institutions in Pakistan. Resource-based learning is the basic right of all citizens. School libraries support teaching and learning with best available information resources. In Pakistan, fewer studies have reported the status of school libraries, and keeping in view the significance of early education, the present study highlights the situation through a qualitative lens. Design/methodology/approach: For an in-depth analysis of the situation, qualitative research approach was used. The data were collected through interviews and observation technique. Additionally, focus groups were conducted with the students of grade IX and X to find their school libraries' perceptions. Findings: The findings revealed that the overall status of school libraries was unsatisfactory. Libraries were facing many problems such as lack of staff, budget, place and poor infrastructure issues. It was also found that economic geographical location of schools was not the factor affecting the status of libraries; rather, the schools' head was mainly responsible for the better condition of the libraries. Research limitations/implications: The study has implications for educationists, librarians, library schools and library professional organizations to make effective policies. However, the findings cannot be generalized and can be applicable in a similar context. Originality/value: The study is based on MPhil thesis and is significant to be added in global school librarianship literature.